Evaluation in Nepal: Primary Policy, Uneven Practice and Limited Capacity - Shrestha, Narayan (Journal of Kathmandu BernHardt College, 2023)
The role of evaluation is highly emphasized for evidence-based policy making and effective development governance. However, there is inadequacy of research that assesses the evaluation policy and practice in Nepal. Ritually, one can find the evaluation term being used in conjunction with monitoring in Nepal. Drawing data from literature reviews and self-professional experience of its author, this article argues that the evaluation policy is yet in a primary stage, the practice is uneven and evaluation capacity both at demand and supply side is lagging far behind its professionalism to create an enabling institutional environment of evaluation. Hence, this article tries to explore the evaluation in Nepal with shedding light on the challenges and opportunities facing Nepal’s evaluation ecosystem, examining its progress and the road ahead.